2019
DOI: 10.2355/isijinternational.isijint-2018-721
|View full text |Cite
|
Sign up to set email alerts
|

Looper-gauge Integrated Control in Hot Strip Finishing Mill Using Inverse Linear Quadratic Theory

Abstract: Hot strip rolling is a significant process in the fields of manufacturing and processing. In order to further improve the control accuracy of looper angle, strip tension and gauge in hot strip finishing mill, an innovative looper-gauge integrated control scheme is developed in this paper. Based on the inverse linear quadratic (ILQ) theory, a proposed control scheme is designed for the looper-gauge integrated system. First, considering the numerous interactions between looper angle, strip tension and gauge, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Most studies on rolling mill vibration focus on a single vibration system, such as vertical, horizontal, or torsional vibration. For instance, Sun et al considered the interaction between strip tension and thickness and analyzed the effect of multiple-source external disturbance on rolling mill vibration; they established a vertical vibration model of the rolling mill and further improved the control accuracy of tension and thickness of the hot rolling mill through optimization design [4]. Fan et al analyzed and calculated the structural stability of hot rolling mill rolls and revealed that the gap between the framework and rolling mill rolls can cause the phenomenon of "vibration jump," which destroys the balance of a rolling mill system [5].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on rolling mill vibration focus on a single vibration system, such as vertical, horizontal, or torsional vibration. For instance, Sun et al considered the interaction between strip tension and thickness and analyzed the effect of multiple-source external disturbance on rolling mill vibration; they established a vertical vibration model of the rolling mill and further improved the control accuracy of tension and thickness of the hot rolling mill through optimization design [4]. Fan et al analyzed and calculated the structural stability of hot rolling mill rolls and revealed that the gap between the framework and rolling mill rolls can cause the phenomenon of "vibration jump," which destroys the balance of a rolling mill system [5].…”
Section: Introductionmentioning
confidence: 99%